2018
DOI: 10.1016/j.drugalcdep.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Relapse to smoking following release from smoke-free correctional facilities in Queensland, Australia

Abstract: Relapse to smoking after release from smoke-free prisons is common, but many who relapse smoke less than before incarceration, suggesting that smoke-free prison policies may reduce post-release tobacco smoking. There is a need for tailored, evidence-based tobacco cessation interventions for people recently released from prison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…During data collection for a broader study investigating return to smoking following release from smoke‐free prisons in Queensland, reports of teabacco use in Queensland's prisons emerged among several participants. One participant who described making teabacco cigarettes from nicotine lozenges while incarcerated, and who was no longer serving a community corrections order, agreed to meet with researchers in a private location in the community to create samples for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…During data collection for a broader study investigating return to smoking following release from smoke‐free prisons in Queensland, reports of teabacco use in Queensland's prisons emerged among several participants. One participant who described making teabacco cigarettes from nicotine lozenges while incarcerated, and who was no longer serving a community corrections order, agreed to meet with researchers in a private location in the community to create samples for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although 114 participants completed the survey in phase one of the study , researchers were not initially aware of the prevalent nature of teabacco use in Queensland prisons, and so structured prompts measuring teabacco use were only added to the survey after 32 participants had already taken part in the study. As a result, quantitative data on teabacco use were available for 82 participants (described throughout as ‘survey participants’).…”
Section: Resultsmentioning
confidence: 99%
“…During data collection for a broader study using a survey to investigate return to smoking following release from smoke‐free prisons in Queensland , reports of teabacco use unexpectedly emerged. In response, we added further structured teabacco‐related prompts to the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted in the USA has found that between 60%25 26 and 74%27 of former smokers released from smoke-free prisons relapse to smoking within 24 hours of release, and 97% relapse within 6 months of release 26. Similarly, in a recent Australian study, 72% of people released from smoke-free prisons relapsed to smoking on the day of release, and 94% relapsed within 2 months of release 28. A systematic review29 of prison-based smoking cessation interventions found that correctional smoke-free policies result in short-term smoking abstinence only and, on their own, are insufficient to maintain long-term smoking cessation after release from prison.…”
Section: Introductionmentioning
confidence: 94%